2019
DOI: 10.1002/14651858.cd012247.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Buffered solutions versus 0.9% saline for resuscitation in critically ill adults and children

Abstract: Bu ered solutions versus 0.9% saline for resuscitation in critically ill adults and children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
29
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 43 publications
(42 citation statements)
references
References 95 publications
5
29
0
2
Order By: Relevance
“…This vehicle bypassed the problem of a bicarbonate-based buffer being affected by respiratory, metabolic, or renal status during pancreatitis, and also that of a phosphate buffer reacting with and neutralizing the administered calcium before it reacted with NEFA. Our approach of using saline (pH 7.4) as a vehicle thus made the study agnostic to the pH in vivo, and is in agreement with a recent meta-analysis covering studies with >20,000 critically ill patients, which concluded that buffered solutions do not provide any survival benefit over normal saline [14].…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…This vehicle bypassed the problem of a bicarbonate-based buffer being affected by respiratory, metabolic, or renal status during pancreatitis, and also that of a phosphate buffer reacting with and neutralizing the administered calcium before it reacted with NEFA. Our approach of using saline (pH 7.4) as a vehicle thus made the study agnostic to the pH in vivo, and is in agreement with a recent meta-analysis covering studies with >20,000 critically ill patients, which concluded that buffered solutions do not provide any survival benefit over normal saline [14].…”
Section: Discussionsupporting
confidence: 84%
“…Lactate infusion reduces the drop in serum bicarbonate [8] and may protect from acidosis. Recently, a Cochran database study of evidence concluded that buffered solutions do not provide any benefit over 0.9% saline in reducing in hospital mortality among critically ill patients with a high degree of certainty [14]. Collectively, these suggest that the benefits of RL are noted in early severe pancreatitis and may be from a mechanism other than its being buffered or containing lactate.…”
Section: Introductionmentioning
confidence: 99%
“…This beneficial effect was replicated in non-critically ill patients and in the perioperative setting 75 , 76 . However, three systematic reviews of studies in adults and children did not demonstrate reduced rates of AKI or mortality with balanced crystalloids compared with saline in pooled analyses 79 81 . Given the possible harm caused by the use of 0.9% saline we recommend using balanced fluids, unless there is an indication for other types of fluid (e.g.…”
Section: Prevention and Management Of Akimentioning
confidence: 99%
“…With normal saline being associated with unwarranted effects such as hyperchloremic acidosis and possibly increased risk of acute kidney injury, use of the more recently introduced buffered solutions has steadily increased 8 . However, clinical practice guidelines do not distinguish between the different types of buffered solutions 9,10 . As buffered salt solutions have varying compositions, considering them as a ‘class’ of fluid could potentially cause for misinterpretation of individual effects.…”
Section: Introductionmentioning
confidence: 99%